From research to practice: the application of NIOSH model ergonomic program in a healthcare setting. - Halpern M (Journal of the Association of Occupational Health Professionals in Healthcare)
NIOSH guidelines do not address ergonomic concerns related to patient safety. Thus, the ergonomic concerns in health-care go beyond musculoskeletal injuries.The National Institute for Occupational Safety and Health (NIOSH) published guidelines for setting up a good ergonomics program that focuses on prevention of the work-related musculoskeletal disorders in the manufacturing and service industries. This pilot study applied the NIOSH model in a specialty hospital and attempted to examine its relevance to healthcare settings.With very few recordable musculoskeletal injuries, the program was set up in a pathology department where management was willing to collaborate rather than where a need was urgent. The program was therefore set as a stand-alone and adapted to address ergonomic issues related to computer terminals in the lab and offices. A task force was set up and assessed the design of the computer workstations using a standard checklist, musculoskeletal symptoms were surveyed and a series of focus groups and training sessions in Healthy Computing were conducted for labor and management. Products were selected to address the ergonomic deficiencies noted in the design of the workstations.The action steps that could be implemented during the project were compared against the guidelines of the NIOSH model ergonomics program. The pilot study revealed that of 41 items listed in NIOSH model, 30 (73 percent) were applicable to the hospital environment. However, the ergonomic concerns in healthcare go beyond musculoskeletal injuries of the care providers, and the NIOSH guidelines do not address ergonomic concerns related to patient safety. Other criteria may have to serve for selecting an intervention site and assessing the impact of the program. Three conclusions can be drawn: 1) the impact of the ergonomic program may not be manifested in OSHA logs but rather in reduction of lost work time due to non-workrelated health problems; 2) to make the ergonomic program more effective, link it to patient safety and risk management; and 3) more research is needed to link the ergonomic concerns of both employees and patients in a healthcare setting.